2021
DOI: 10.3390/su13063581
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Customer Responses to Service Failures during the COVID-19 Pandemic for Sustained Restaurant Businesses: Focusing on Guanxi

Abstract: Due to the COVID-19 pandemic, restaurants worldwide, including China, have been forced to protect public health by following food safety standards and adapting to the necessary social distancing practices. Accordingly, restaurant diners who are concerned about food safety and unsure of whether it is truly safe to dine out, put more importance on the entire stages of service consumption. Restaurants must make their best efforts to minimize service failures in their service provision process and outcomes. Given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…The hygiene standards in tourism services are decisive for travel risk perception, which is confirmed by the research of Hussain et al [74], Radic et al [75], Chan et al [76], Taylor [77], Yost and Cheng [78], Al-Marzouqi and Yahia [79], Zhang et al [80], Zhong et al [81], Davahli et al [82], Aydin et al [83] and Abbas et al [84]. These researchers, representing various scientific disciplines, from the perspective of their own experience, knowledge, research methods used in a given discipline, pointed to various aspects of consumer expectations towards service providers and the physical environment in which a service takes place.…”
Section: Resultsmentioning
confidence: 67%
“…The hygiene standards in tourism services are decisive for travel risk perception, which is confirmed by the research of Hussain et al [74], Radic et al [75], Chan et al [76], Taylor [77], Yost and Cheng [78], Al-Marzouqi and Yahia [79], Zhang et al [80], Zhong et al [81], Davahli et al [82], Aydin et al [83] and Abbas et al [84]. These researchers, representing various scientific disciplines, from the perspective of their own experience, knowledge, research methods used in a given discipline, pointed to various aspects of consumer expectations towards service providers and the physical environment in which a service takes place.…”
Section: Resultsmentioning
confidence: 67%
“…There has also been a disruption in the supply chain due to widespread business shutdown (Zhang et al 2021a ; Wu and Zhu 2021 ). Supply chain disruptions and lower raw material demand due to decreased production have also reduced energy usage, hence lowering energy demand (Chaar and Bromwich 2021 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Emerging market economies like India, China, and Brazil were also affected by the COVID-19 pandemic’s first wave of infected individuals (Clampit et al 2021 ). The COVID-19 pandemic is one of the biggest macroeconomic shocks that affects both established and developing economies, according to Zhang et al ( 2021a , b , c , d ). Only a single market or developing markets (Tomé et al 2022 ) are considered by contemporary academics, who do not consider both developed and developing countries simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has already demonstrated that service failure and recovery influences consumers’ perceptions of fairness (Gelbrich and Roschk, 2011), their emotional responses (Valentini et al , 2020) and their repurchase (Kanuri and Andrews, 2019), forgiveness and retaliation intentions (Atav et al , 2021), satisfaction and word-of-mouth (WOM) (Bonifield and Cole, 2008; Hoegreve et al , 2017). Cultural values have also been the focus of extensive research, which investigated their impact on consumer perception and behavior (El Jurdi and Houjeir, 2020; Nath, 2018; Moro et al , 2020) and their relation to service failure and recovery (Matos et al , 2011; Schoefer et al , 2019; Sengupta, 2020; Zhang et al , 2021).…”
Section: Introductionmentioning
confidence: 99%